On selection of foxes for enhanced aggressiveness and its correlated implications - L. N. Trut; A. V. Kharlamova; A. V. Vladimirova; Yu. E. Herbeck (Вавиловский журнал генетики и селекции, 2017)
The results of a 35-year selection of foxes for aggressive response to humans are reported. Averaged estimates of the phenotypic manifestation of aggressiveness in all selection generations are presented. The dynamics of these estimates shows that the phenotypic response to the selection was obvious only in the first 12 generations. Subsequent selection did not alter the mean aggressiveness score. Analysis of variance was performed for the intergroup variability (among descendants of different mothers) and intragroup variability (among the offspring within a family). The intragroup variability was constantly low. Most likely, the trait is stabilized by maternal prenatal and early neonatal factors. The general tendency in the dynamics of intergroup variability is that it does not decrease over time during selection, no matter how long the population has been under it. It follows from the statistical indices of the phenotypic similarity between parents and offspring that additive interactions are insufficient for the explanation of the persisting variability. The contribution of epistatic interactions is not ruled out, though. Emphasis is laid on the correlated consequences of the selection for aggressiveness and their coordination with the consequences of the selection in the opposite direction, for elimination of aggressive response to humans, or for tameness. The parallelism of correlated changes in the selection in contrasting directions is illustrated by the examples of some physiological and morphological traits. The phenomenon is discussed in the light of classical notions of the resource of cryptic genetic variation and the role of selection in its phenotypic manifestation. Its interpretation also invokes molecular data pointing that some genetic pathways may regulate parameters of both aggression and tameness and that the selection processes in both directions may have some genetic targets in common.